Caffeine ingestion before exercise improves prolonged intermittent-sprint performance of team-sport athletes in normobaric hypoxia - Li, Wei; Cao, Zuojun; Chang, Jie; Xue, Ruiguo; Liu, Jue; Guo, Li; Cao, Yinhang; Girard, Olivier (Frontiers in Nutrition, 2026)
PurposeTo investigate whether caffeine ingestion before exercise enhances performance during a prolonged intermittent-sprint test (IST) under hypoxic conditions simulating team-sport activity.MethodsIn a randomized, double-blind, placebo-controlled crossover design, fifteen (five females) team-sport athletes (21 ± 2 years; peak oxygen uptake: 51.9 ± 3.4 ml/kg/min) completed two IST sessions in normobaric hypoxia (inspired oxygen fraction: 16.5 ± 0.2%), separated by 7 days. Sixty minutes before each session, participants ingested either 6 mg/kg caffeine or a placebo. The IST, performed on a cycle ergometer, consisted of two 40-min halves. Each half included twenty 2-min blocks, comprising an 8-s all-out sprint, 100 s of active recovery at 35% peak oxygen uptake, and 12 s of passive rest.ResultsTotal work done was significantly greater with caffeine, increasing by 6.2% in the first half (154 ± 26 vs. 145 ± 27 kJ) and a 5.3% increase in the second half (138 ± 20 vs. 132 ± 22 kJ) compared to placebo (all p < 0.05). Caffeine also significantly increased both peak and mean power output (all p < 0.05). Blood lactate concentrations were higher in both halves with caffeine, while ratings of perceived exertion and breathing difficulty were significantly lower in the second half compared to placebo (all p < 0.05).ConclusionA moderate dose of caffeine intake before exercise significantly enhances prolonged intermittent-sprint performance in competitive team-sport athletes under moderate normobaric hypoxia.